The psychology of the female athlete: how mental health and wellness mediate sports performance, injury and recovery - Herrero, C. P.; Jejurikar, N.; Carter, C. W. (Annals of joint, 2021)
The increase in athletic participation of girls and women over the last half-century has brought into focus the need to better understand the psychology of female athletes. This review explores various non-physical factors that contribute to athletic success, such as resilience, mindfulness and sleep. The role of anxiety and depression in sport-related injury is another key issue that those invested in an athlete`s training must be able to recognize and manage. Additionally, disordered eating and the harmful effects of social media affect females differently and at a higher rate than their male counterparts. Lastly, understanding how the female athlete views injury and recovery may allow us to successfully return injured athletes to sport. The goal of this article is to provide an overview of how a female athlete`s mental and emotional well-being affect her athletic performance, injury risk and recovery following sports-related injury.